A revision of Welfia (Arecaceae) - Henderson, Andrew; Villalba, Isabel (Phytotaxa, 2013)
A taxonomic revision of the neotropical palm genus Welfia based on morphological data and morphometric methods was carried out. One hundred and five herbarium specimens were scored for one qualitative variable and 19 quantitative variables. Based on the qualitative variable, fruit shape, two species are recognized. One (W. regia) is widely distributed in Central America and northwestern South America from Nicaragua to Colombia and Ecuador; the second, described here (W. alfredii) is restricted to a small area of central Peru. Nomenclature, descriptions, and distribution maps are provided for each species, and images of the type specimen of the new species are also provided.